2021
DOI: 10.1136/bmjopen-2020-045851
|View full text |Cite
|
Sign up to set email alerts
|

Treatment preferences for preventive interventions for rheumatoid arthritis: protocol of a mixed methods case study for the Innovative Medicines Initiative PREFER project

Abstract: IntroductionAmidst growing consensus that stakeholder decision-making during drug development should be informed by an understanding of patient preferences, the Innovative Medicines Initiative project ‘Patient Preferences in Benefit-Risk Assessments during the Drug Life Cycle’ (PREFER) is developing evidence-based recommendations about how and when patient preferences should be integrated into the drug life cycle. This protocol describes a PREFER clinical case study which compares two preference elicitation me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…This study is part of a case study for the Innovative Medicines Initiative project ‘PREFER’ (Patient Preferences in Benefit-Risk Assessments during the Medical Product Lifecycle), which aimed to develop evidence-based recommendations on how and when preference studies can inform decision-making during drug development. 14 The case study protocol 27 and other results from the case study 21 have been published previously.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study is part of a case study for the Innovative Medicines Initiative project ‘PREFER’ (Patient Preferences in Benefit-Risk Assessments during the Medical Product Lifecycle), which aimed to develop evidence-based recommendations on how and when preference studies can inform decision-making during drug development. 14 The case study protocol 27 and other results from the case study 21 have been published previously.…”
Section: Methodsmentioning
confidence: 99%
“…The selection of treatment attributes included in the PTT was informed by a literature review, 17 a qualitative study and an attribute ranking survey. 27 The final attributes ( table 1 ) were agreed upon by an international team of clinical researchers, consultant rheumatologists, preference elicitation experts and patient partners. Attribute levels were estimated with input from clinical experts, including researchers leading the development and/or clinical trials of preventive treatments for RA.…”
Section: Methodsmentioning
confidence: 99%
“…Further investigation is needed to assess preferences in different countries with different types of healthcare provision and also in low and middle income countries. Existing choice-based studies have not yet identified participant characteristics (e.g., gender; health literacy; and numeracy) associated with preference heterogeneity (52), though this is currently under investigation (58).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the protocol of a stated choice survey employing both a DCE and a probabilistic threshold technique to assess preferences for preventive treatments for RA has been published (58). That study recruits large samples of the general population via survey panels in the UK, Germany and Romania, and also recruits FDRs of confirmed RA patients.…”
Section: Quantitative Investigationsmentioning
confidence: 99%
“…The Patient Preferences in Benefit-Risk Assessments during the Drug Life Cycle (PREFER) project aims to assess when and how patient preferences on benefits and risks should be incorporated into treatment decisions (46). Through PREFER, a multitude of preference studies have been conducted across chronic conditions, with consideration to the inclusion of patient preferences in the process of clinical trials and drug development, from pre-approval of treatments to post-authorization (46)(47)(48). Both the FDA and PREFER have highlighted the promise and potential value of including patient preferences when designing clinical trials.…”
Section: Discussionmentioning
confidence: 99%